Advancing the Certified in Public Health Examination: A Job Task Analysis. (July 2017) - Kurz, Richard S.; Yager, Christopher; Yager, James D.; Foster, Allison; Breidenbach, Daniel H.; Irwin, Zachary
Objectives: In 2014, the National Board of Public Health Examiners performed a job task analysis (JTA) to revise the Certified in Public Health (CPH) examination. The objectives of this study were to describe the development, administration, and results of the JTA survey; to present an analysis of the survey results; and to review the implications of this first-ever public health JTA. Methods: An advisory committee of public health professionals developed a list of 200 public health job tasks categorized into 10 work domains. The list of tasks was incorporated into a web-based survey, and a snowball sample of public health professionals provided 4850 usable responses. Respondents rated job tasks as essential (4), very important (3), important (2), not very important (1), and never performed (0). Results: The mean task importance ratings ranged from 2.61 to 3.01 (important to very important). The highest mean ratings were for tasks in the ethics domain (mean rating, 3.01). Respondents ranked 10 of the 200 tasks as the most important, with mean task rankings ranging from 2.98 to 3.39. We found subtle differences between male and female respondents and between master of public health and doctor of public health respondents in their rankings. Conclusion: The JTA established a set of job tasks in 10 public health work domains, and the results provided a foundation for refining the CPH examination. Additional steps are needed to further modify the content outline of the examination. An empirical assessment of public health job tasks, using methods such as principal components analysis, may provide additional insight.